Fluid Boundaries and Moving Targets: Midwife Leaders' Perspectives on Continuing Professional Education. (June 2020) - Røseth, Idun; Austenå, Halvor; Sommerseth, Eva; Dahl, Bente; Lyberg, Anne; Bongaardt, Rob
In this study, we aim to understand midwife leaders' perspectives on continuing professional education among midwives in their work unit. We used a phenomenological perspective and method in the process of interviewing the participants and analyzing the data. Five midwife leaders who worked in large maternity wards and had considerable experience as managers were recruited. Results revealed three essential constituents: (a) constraints and the individualization of continuing professional education, (b) normal and at-risk births: fluid boundaries and moving targets, and (c) a personal approach: dimensions of control and trust-driven leadership. We discuss these findings in relation to current research and perspectives on how professional cultures and leadership impact continuing professional education and knowledge management, revealing possible implications to further promote professional development in public health organizations. We conclude that midwife leaders' views on continuing professional education as practical skills training may hinder professional communication and knowledge development in maternity care.